Hybrid Electric Vehicles Energy Management Strategies - Onori, Simona; Serrao, Lorenzo; Rizzoni, Giorgio; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2016)
This SpringerBrief deals with the control and optimization problem in hybrid electric vehicles. Given that there are two (or more) energy sources (i.e., battery and fuel) in hybrid vehicles, it shows the reader how to implement an energy-management strategy that decides how much of the vehicle's power is provided by each source instant by instant. Hybrid Electric Vehicles: •introduces methods for modeling energy flow in hybrid electric vehicles; •presents a standard mathematical formulation of the optimal control problem; •discusses different optimization and control strategies for energy management, integrating the most recent research results; and •carries out an overall comparison of the different control strategies presented. Chapter by chapter, a case study is thoroughly developed, providing illustrative numerical examples that show the basic principles applied to real-world situations. The brief is intended as a straightforward tool for learning quickly about state-of-the-art energy-management strategies. It is particularly well-suited to the needs of graduate students and engineers already familiar with the basics of hybrid vehicles but who wish to learn more about their control strategies.
Energy-based Modeling Approach -- The Control Problem for HEVs/PHEVs -- Dynamic Programming -- Pontryagin's Minimum Principle -- Equivalent Consumption Minimization Strategy -- Adaptive ECMS -- Implementation Issues.
Keywords: Control engineering; Automotive engineering; Energy policy; Energy and state; Physics; Thermodynamics; Control and Systems Theory; Automotive Engineering; Energy Policy, Economics and Management; Applied and Technical Physics; Thermodynamics